THE DIVERSITY OF GASTROPODS AND BIVALVES IN MANGROVE FORESTS OF MENDALOK VILLAGE, SUNGAI KUNYIT SUBDISTRICT, MEMPAWAH REGENCY, WEST KALIMANTAN PROVINCE - Rahayu, Gita Yunita; M.Si, Inpurwanto; Rahayu, Sri (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACKThe aim of study is to determine the diversity og gastropods and bivalves in mangrove forests of Mendalok Village, Sungai Kunyit Subdistrict, Mempawah Regency, West Kalimantan Province. This study was conducted for 3 months was divided by using Purposive Random Sampling. Sampling sites into 3 stations, station1 was dominated by Rhizophora, station 2 was dominated by Bruguiera, anda station 3 was dominated by Nypah. Data collected in this study are primary and secondary data. The primary data was obtained through direct measurement at the study stations. This data includes number individuals per-plot, gastropods and bivalves species name, and aquatic environmental characteristics (i.e. temperature, pH, salinity, and substrat). While secondary data was obtained from village profiles. Which were 9 other species groupied into 3 families which were classified into the Gastropod class and 3 other species groupied into 1 family which were classified into the Bivalve class. From all 3 stations, species Cerithidae cingulata (Gastropods class) with the value of Abundance (K) was 24,00 ind/m2. While species Polymesoda erosa (Bivalves class) with the value of Abundance (K) was 2,00 ind/m2.Keyword : Type Composition, Cerithidae ciungalata, Polymesoda erosa